2022
DOI: 10.1155/2022/5090200
|View full text |Cite
|
Sign up to set email alerts
|

Acute Liver Failure following a Single Dose of Atezolizumab, as Assessed for Causality Using the Updated RUCAM

Abstract: Immune checkpoint inhibitors have become major therapeutic agents in oncology over the last few years. However, they are associated with a variety of potentially severe autoimmune phenomena. We present a patient with advanced adenocarcinoma of the lung, who presented with acute liver injury two weeks following his first treatment with atezolizumab, rapidly deteriorating to fulminant liver failure. A thorough evaluation of infectious, vascular, metabolic, and autoimmune etiologies did not yield any results. Liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…For monotherapy, atezolizumab might show the strongest risk signal of hepatic failure. There has been one case of acute hepatic failure reported with atezolizumab 5 ; however, it has been reported that ipilimumab, pembrolizumab, and nivolumab were more associated with liver damage. 17 , 18 Considering that atezolizumab was approved later and its adverse effects have only been identified in recent years, our findings may not be enough to conclude that atezolizumab has the highest risk of hepatic failure among all ICIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For monotherapy, atezolizumab might show the strongest risk signal of hepatic failure. There has been one case of acute hepatic failure reported with atezolizumab 5 ; however, it has been reported that ipilimumab, pembrolizumab, and nivolumab were more associated with liver damage. 17 , 18 Considering that atezolizumab was approved later and its adverse effects have only been identified in recent years, our findings may not be enough to conclude that atezolizumab has the highest risk of hepatic failure among all ICIs.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Recently, some case reports have raised awareness of hepatic failure induced by ICIs. 5 , 6 , 7 A systematic review concluded that the incidence of grade 3 and 4 liver damage induced by ICIs was 0.6%–11% and the incidence of hepatic failure was 0.1%–0.2%. 3 A pharmacovigilance study based on the WHO VigiBase database reported 613 ICI‐associated fatal adverse events from 2009 to January 2018, of which 124 (20.2%) cases were associated with liver damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For monotherapy, atezolizumab showed the strongest risk signal of hepatic failure. There has been one case of acute hepatic failure reported with atezolizumab [5] , however, it has been reported that ipilimumab, pembrolizumab, and nivolumab were more associated with liver damage [15,16] . Considering that atezolizumab was approved later and its adverse effects have only been identi ed in recent years, our ndings may not be enough to conclude that atezolizumab has the highest risk of hepatic failure among all ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Although most ICI-associated liver damage usually presented as mild elevations of liver enzymes, hepatic failure induced by ICIs was rare but potentially life-threatening [3,4] . Recently, some case reports have raised awareness of hepatic failure induced by ICIs [5,6,7] . A systematic review concluded that the incidence of grade 3 and 4 liver damage induced by ICIs was 0.6-11% and the incidence of hepatic failure was 0.1-0.2% [3] .…”
Section: Introductionmentioning
confidence: 99%